Badminton Achievment Coaching for Early Childhood in PB Djarum Kudus (Human Resource Management Study, Finance Management, Training Method, Tools and Infrastructures) - Santoso, Bayu Dwi; Kristiyanto, Agus; Purnama, Sapta Kunta (Journal of Education, Health and Sport, 2019)
This research was aimed to know the tools and infrastructures in PB Djarum Kudus. The type of the research used qualitative research method with case study research type. The subject of the research were athletes, coaches, and management of PB Djarum Kudus. The data collection technique used were interview and observation. The collected data were analyzed by using data reduction technique, data presentment, and conclusion drawing or data verification. The result of the interview and observation which has been done, obtained results that the badminton sport tools and infrastructures owned by PB Djarum Kudus club was very good. Moreover, the planning and procurement of the club tools and infrastructure were done programmatically.According to the results obtained, it could be concluded that the tools and infrastructures owned by PB Djarum Kudus were very adequate. This matter was seen from the availability of tools and infrastructures provided in PB Djarum Kudus were very complete. With this adequate facilities, it could ease the process of coaching the early childhood in PB Djarum Kudus, so it could produce good and talented athletes.